A coupled theory for deformation and phase transformation due to CMAS infiltration and corrosion of thermal barrier coatings. (September 2021) - Xu, Guangnan; Yang, Li; Zhou, Yichun
Highlights: A mechanism-based phase field approach is proposed for the process of phase transition happening in corroded TBCs. The infiltration of CMAS and the extension of monoclinic phase are captured by both model and experiment quantificationally. Out-plane tensile stress σ yy accumulates in the interface between transformed and untransformed regions. The stress induced by phase transition has an inhibiting effect on the evolution of monoclinic phase. Abstract: This work proposes a mechanism-based phase-field approach for tetragonal-to-monoclinic transformation in thermal barrier coatings (TBCs) corroded by calcium-magnesium-alumino-silicates (CMAS). A 2D plate model is established and verified by experiments results of the distribution of CMAS mass density and the extension of the monoclinic phase after different heating times. In addition, the simulation results show that the tensile stress accumulates in the interface between two phases, which can be seen as the motivation for horizontal cracks in TBCs. The theoretical model presented here shows excellent capacities to capture the evolution of the monoclinic phase in TBCs corroded by CMAS.